Effects of three modes of physical activity on physical fitness and hematological parameters in older people with sarcopenic obesity: A systematic review and meta-analysis - Zhuang, Min; Jin, Mengdie; Lu, Tijiang; Lu, Linqian; Ainsworth, Barbara E.; Liu, Yu; Chen, Nan (Frontiers in Physiology, 2022)
Objective: This systematic review and meta-analysis assessed the effects of three modes of physical activity (PA) (aerobic training [AT], resistance training [RT], and aerobic combined with resistance training [MT]) on body composition (body weight [BW], body mass index [BMI] and percentage of body fat [BF%]), muscle mass (skeletal muscle mass [SM], appendicular skeletal muscle mass [ASM] and appendicular skeletal muscle mass index [ASMI]), muscle strength (handgrip strength [HG] and knee extension strength [KES]), physical performance (gait speed [GS]) and hematological parameters (inflammatory markers, insulin-like growth factor 1 [IGF-1] and lipid profiles) in older people with sarcopenic obesity (SO). Methods: We searched all studies for PA effects in older people with SO from six databases published from January 2010 to November 2021. Two researchers independently screened studies, extracted data according to inclusion and exclusion criteria, and assessed the quality of included studies. Pooled analyses for pre-and post- outcome measures were performed by Review Manager 5.4. We calculated a meta-analysis with a 95% confidence interval (95% CI) and the standardized mean differences (SMD). Results: 12 studies were analyzed. There were 614 older people (84.9% female) with SO, aged 58.4 to 88.4 y. Compared with a no-PA control group, AT decreased BW (SMD=-0.64, 95%CI: -1.13 to -0.16, p=0.009, I² = 0%) and BMI (SMD=-0.69, 95% CI:-1.18 to -0.21, p=0.005, I²= 0%); RT improved BF% (SMD=-0.43, 95%CI:-0.63 to -0.22, p<0.0001, I²=38%), ASMI (SMD=0.72, 95%CI:0.24 to 1.21, p=0.004, I²=0%), ASM (SMD=-0.94, 95%CI: -1.46 to-0.42, p=0.0004), HG (SMD=1.06, 95%CI: 0.22 to 1.91, p=0.01, I²=90%) and KES (SMD=1.06, 95%CI:0.73 to 1.39, p<0.00001 , I²= 14%); MT improved BMI (SMD=-0.77, 95%CI: -1.26 to -0.28, p=0.002, I²=0%), BF% (SMD=-0.54, 95%CI:-0.83 to -0.25, p=0.0003, I²=0%), ASMI (SMD=0.70, 95%CI:0.22 to 1.19, p=0.005, I²=0%) and GS (SMD=0.71, 95%CI: 0.23 to 1.18, p=0.004, I²=37%). PA increased IGF-1 (SMD=0.38, 95% CI: 0.11 to 0.66, p=0.006, I²=0%), but had no effect on inflammatory markers and lipid profiles. Conclusion: PA is an effective treatment to improve body composition, muscle mass, muscle strength, physical performance, and IGF-1 in older people with SO.